Human antibody reaction against recombinant salivary proteins of Phlebotomus orientalis in Eastern Africa. - Petra Sumova; Michal Sima; Tatiana Spitzova; Maha E Osman; Anderson B Guimaraes-Costa; Fabiano Oliveira; Dia-Eldin A Elnaiem; Asrat Hailu; Alon Warburg; Jesus G Valenzuela; Petr Volf (Public Library of Science (PLoS), 2018)
Background Phlebotomus orientalis is a vector of Leishmania donovani, the causative agent of life threatening visceral leishmaniasis spread in Eastern Africa. During blood-feeding, sand fly females salivate into the skin of the host. Sand fly saliva contains a large variety of proteins, some of which elicit specific antibody responses in the bitten hosts. To evaluate the exposure to sand fly bites in human populations from disease endemic areas, we tested the antibody reactions of volunteers' sera against recombinant P. orientalis salivary antigens. Methodology/principal findings Recombinant proteins derived from sequence data on P. orientalis secreted salivary proteins, were produced using either bacterial (five proteins) or mammalian (four proteins) expression systems and tested as antigens applicable for detection of anti-P. orientalis IgG in human sera. Using these recombinant proteins, human sera from Sudan and Ethiopia, countries endemic for visceral leishmaniasis, were screened by ELISA and immunoblotting to identify the potential markers of exposure to P. orientalis bites. Two recombinant proteins; mAG5 and mYEL1, were identified as the most promising antigens showing high correlation coefficients as well as good specificity in comparison to the whole sand fly salivary gland homogenate. Combination of both proteins led to a further increase of correlation coefficients as well as both positive and negative predictive values of P. orientalis exposure. Conclusions/significance This is the first report of screening human sera for anti-P. orientalis antibodies using recombinant salivary proteins. The recombinant salivary proteins mYEL1 and mAG5 proved to be valid antigens for screening human sera from both Sudan and Ethiopia for exposure to P. orientalis bites. The utilization of equal amounts of these two proteins significantly increased the capability to detect anti-P. orientalis antibody responses.